Culture and growth of a marine harpacticoid, pararobertsonia sp. in different salinity and temperature - K. Zaleha,; Farahiyah Ilyana Jamaludin, (Universiti Kebangsaan Malaysia, 2010)
Copepods play a major role as food link for larger animals and it is also important as a live food source for the aquaculture industry. There are only few reports on the influence of temperature and salinity towards the growth and development of tropical copepods. In this study, the effect of temperature (5 and 25¡C) and salinity (5, 10, 25 and 30 psu) on population growth and density of a marine harpacticoid, Pararobertsonia sp. in a laboratory condition is investigated. The species was first obtained from seagrass samples from Merchang estuary, Terengganu, which receives seawater from the South China Sea. It has been cultured in the laboratory condition through generations. The findings show that there is a significant difference (P<0.05) detected between the salinity treatment and it shows that difference in salinities give different effects on the population number of the harpacticoids cultured in the same temperature (25 ± 1¡C). On the other hand, harpacticoids reared in cold temperature (5 ± 1¡C) did not survive the condition. Harpacticoids reared in 25 psu salinity show the highest population density (mean of 3.7 ind./ml), but the most stable population growth is shown in 35 psu treatment as shown by its high value of maximum specific growth rate (K). From this experiment, it can be concluded that 35 psu and temperature of 25 ± 1¡C is the optimum condition for the maximum production of a tropical Pararobertsonia sp. in the laboratory condition.